Multimorbidity among Pregnant Women in India: National and State-level Burden and Socio-demographic Variations - Sreeharshita Malla; Varun Agiwal; Sirshendu Chaudhuri (Preventive Medicine: Research & Reviews, 2024)
Objectives: To estimate the national and state-level burden of multimorbidity in pregnancy in India and to assess the burden in different socio-demographic strata. Methods: The study utilised National Family Health Survey 5 data, focusing on pregnant women, and assessing eight morbidity conditions. Multimorbidity was defined as the presence of at least two out of these conditions. Descriptive statistics were used to show the national and state wise burden of the condition and the distribution in different socio-demographic strata. Results: The authors analysed the data from 28,191 pregnancies, with participants having a mean age of 25.1 years (standard deviation 4.9 years). The prevalence of multimorbidity in pregnancy was found to be 13.7 per 1000 pregnant women, with notable regional variations. The North-Eastern states, such as Nagaland (67.3), Meghalaya (56.4), Mizoram (28.6) and Tripura (25.6), exhibited higher prevalence. Tribal population (23.9) and women in the poorest wealth index category (16.3) had higher prevalence. Conclusion: The prevalence of multimorbidity appears to be relatively low in the Indian context, although it is likely to be underestimated.